2018
DOI: 10.1002/ajmg.a.61006
|View full text |Cite
|
Sign up to set email alerts
|

Primary muscle involvement in a 15‐year‐old girl with the recurrent homozygous c.362dupC variant in FKBP14

Abstract: Kyphoscoliotic Ehlers‐Danlos syndrome associated with FKBP14 (FKBP14‐kEDS) is an ultrarare autosomal recessive disorder reported in less than 30 individuals so far. In its original description, emphasis was put on the mild muscle involvement. Further reports confirm that FKBP14‐kEDS is distinguishable from primary muscle disorders by the lack of progressive muscle disease. We report a 15‐year‐old girl with FKBP14‐kEDS as a result of the recurrent c.362dupC variant, who also showed severe involvement of the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…hyperextensibility) (Kirschner et al, 2005;Voermans et al, 2008;Bönnemann, 2011). In kEDS-FKBP14 muscle weakness does not seem to progress and muscle MRI shows unspecific changes of myopathy (Baumann et al, 2012;Castori et al, 2018;Dordoni et al, 2016;Giunta et al, 2018). ously (Baumann et al, 2012), and is confirmed in this report.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…hyperextensibility) (Kirschner et al, 2005;Voermans et al, 2008;Bönnemann, 2011). In kEDS-FKBP14 muscle weakness does not seem to progress and muscle MRI shows unspecific changes of myopathy (Baumann et al, 2012;Castori et al, 2018;Dordoni et al, 2016;Giunta et al, 2018). ously (Baumann et al, 2012), and is confirmed in this report.…”
Section: Discussionsupporting
confidence: 81%
“…This study reports the clinical and molecular characteristics of three nonrelated individuals with kEDS-FKBP14 and brings the total number of reported individuals to 40 individuals from 36 families (Alazami et al, 2016;Aldeeri et al, 2014;Bursztejn et al, 2017;Castori et al, 2018;Conversano et al, 2020;Dordoni et al, 2016;Giunta et al, 2018;Murray et al, 2014;Ruiz-Botero et al, 2019;Sainio et al, 2022;Semyachkina et al, 2021). Mild to moderate learning problems and/or speech problems have been reported in 22.5% (n = 9) and notably, 77.8% of these individuals (n = 7, not reported in 1 and absent in 1) also had hearing impairment which could negatively influence language development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGex is designed to judiciously leverage the vast GeneCards Suite knowledgebase to address various clinical genetics requirements and workflows. TGex was shown to quickly identify causal mutations of rare disease cases, both when the causal variant was previously documented [72], and in the discovery of novel mutations through prioritization of potential variants of uncertain significance (VOUSes) [73]. Even for patients diagnosed with a known genetic disorder and an identified mutation, TGex has been used to examine phenotypic variability and identify modifier mutations and genes on top of established findings [74].…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, TGex and VarElect have been widely adopted for clinical genetics analysis in various academic institutions, genetic medical centers and hospitals world-wide, with usage volumes ranging from research groups focusing on a handful of patients to genetic centers routinely analyzing hundreds of cases per month [54, 7278, 8095]. Our interactions with a diversity of clinical genetics users impel us to deliver frequent community-driven improvements.…”
Section: Resultsmentioning
confidence: 99%